Can’t Seem to Verb Construction in English - Mija Kim (Journal of cognitive science, 2023)
This study addresses the can’t seem to verb construction from a perspective of Construction Grammar. The most salient issue in this construction is the mismatch between the syntactic structure and its meaning. This construction has the superficial syntactic form corresponding to the linear order of can, not, seem, even though its interpretation is derived from a combination of seem, can, not. A variety of analyses in previous literature focus on whether these three elements are compositional, resulting in an idiomatic expression or not. This study aims to identify the syntactic and semantic properties of this construction with the help of raw frequency and collostructional analyses. Focusing on the results presented, the study argues that this construction forms its own unique construction with the prototypical meaning of representing a speaker’s mild feeling of frustration regarding either the lack of ability or improbability of finding something successfully, which is derived from this syntactic form. This interpretation is supported by collostructional analysis. In addition, this study provides a variety of characteristics of this construction. KCI Citation Count: 0